Effects of in-ovo injection of Yu ping feng polysaccharides on growth performance, intestinal development, and immunity in broiler chickens - Li-Gang Xue; Tian-Kui Guo; Juan Wang; Yu-Quan Shan; Li Guo; Dong-Xing Zhang; Zhong Wei; Dan Wang (Poultry Science)
This study aimed to investigate the effects of the in-ovo injection of Yu Ping Feng polysaccharides (YPF) on the immunological development, hatchability, growth performance, intestinal tissue development, intestinal IgA+ cell distribution, and intestinal secretory IgA (SIgA) production in broiler chicken. Herein, 800 chicken embryos were randomly divided into Astragalus polysaccharide (APS), Atractylodes macrocephala polysaccharide (ATR), YPF, and normal saline (control) injection groups—polysaccharide injection, 0.5 mL of 4 mg/mL polysaccharide; normal saline injection, 0.5 mL. The related indexes of hatched chicks were detected, and there were 5 repeats in each group. Compared with the other three groups, the in-ovo YPF injection did not affect the hatching rate of chicken embryos; however, the initial body weight of hatchlings significantly increased and the feed conversion ratio decreased. Additionally, at each time point, the intestinal villus height (VH) of the chicks in the YPF group increased, whereas no notable difference was observed in the crypt depth (CD), resulting in a higher VH/CD ratio. Furthermore, the YPF group exhibited a statistically significant increase in intestinal IgA+ cell count and flushing fluid SIgA level throughout various time periods compared with those in the other three groups. Additionally, the expression of intestinal mucosal immune cytokines, including interleukin (IL)-2, IL-4, IL-6, and interferon-γ, were markedly increased in the duodenum and ileum of the YPF group. Moreover, the analysis of immune development revealed that their serum levels in the polysaccharide-injected groups were also increased, with the YPF groups exhibiting superior performance than the APS and ATR groups and encouraging the development of T and B lymphocytes in the spleen and peripheral blood mononuclear cells. Altogether, the findings of this study demonstrate that the in-ovo injection of YPF can improve the growth performance, intestinal tissue development, and immune system of the broiler chicks.